Managing Government Property Assets: The Main Issues From The Malaysian Perspective - Abdullah, Shardy; Abdul Razak, Arman; Hanafi, Mohd Hanizun; Salleh, Mohd Najib (Journal of Techno-Social, 2011)
The Malaysian federal government is largely responsible towards providing several facilities to the community. The development of various types of property assets which encompasses buildings and infrastructure such as office buildings, roads, bridges and others, has proved that the government is really committed in executing its responsibility. From time to time, the number of property assets that were developed by the government is increasing parallel with the government's desire to stabilize its service quality. Nevertheless, in managing those property assets, the government currently is facing a mixture of problems and pitfalls such as the increase of property management and maintenance costs, the occurrence of incompatible maintenance programs, underutilization of property, end-user dissatisfaction and others. Following this scenario, the study was done with the main objective is to determine the management factors that are hindering the implementation of property management activities. A total of 67 respondents from ministries and technical departments were selected. The data was collected through a survey using questionnaire forms. The collected data was then analyzed using quantitative approaches such as frequency analysis method, mean analysis, relative important index as well as others. Results from the analysis show that there are 5 main management issues in managing Malaysian government owned property assets. Those issues are lack of proper property unit/department within a ministry, lack of expertise, lack of proper strategies, lack of proper management procedure and lack of IT usage.